If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -17 = x + -1 Reorder the terms: -17 + 3x = x + -1 Reorder the terms: -17 + 3x = -1 + x Solving -17 + 3x = -1 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -17 + 3x + -1x = -1 + x + -1x Combine like terms: 3x + -1x = 2x -17 + 2x = -1 + x + -1x Combine like terms: x + -1x = 0 -17 + 2x = -1 + 0 -17 + 2x = -1 Add '17' to each side of the equation. -17 + 17 + 2x = -1 + 17 Combine like terms: -17 + 17 = 0 0 + 2x = -1 + 17 2x = -1 + 17 Combine like terms: -1 + 17 = 16 2x = 16 Divide each side by '2'. x = 8 Simplifying x = 8
| 16x^4-64=0 | | 2x+11=43-3x | | 15-2(4)= | | 4n+12=4n+12 | | h+11.3=-11.3 | | 15-2(2)= | | 3x-5=72 | | a(n+1)= | | h=-8t^2+63 | | F(x)=62+35log(11-4) | | 12x+3=32 | | -6+2(10)= | | 0.6x-14=0.4x | | f(x)=9x^2+3x-2 | | 9x+3y-36=0 | | -6+2(2)= | | 9x^4+9x=0 | | 2h=-16t^2+126t | | 2(15)-15= | | 2(9)-15= | | 5(x+3)-8(x+3)+x(5-2)= | | 3+5=57 | | 2y-8+y-5=13 | | 18x-8y=14fory | | -2=17-g | | (k+7)x=5k+3-6y | | 45-1(4)= | | 8x-12=18+7x | | 12-2(6)= | | f(x)=5x^2+40x-5 | | 12-2(3)= | | 45-99x=95-591x |